2023
DOI: 10.3847/1538-4357/ace4c0
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Magnetic Fields in Spiral Galaxies: A Radio and Far-infrared Polarimetric Analysis

William Jeffrey Surgent,
Enrique Lopez-Rodriguez,
Susan E. Clark

Abstract: We propose and apply a method to quantify the morphology of the large-scale ordered magnetic fields (B-fields) in galaxies. This method is adapted from the analysis of Event Horizon Telescope polarization data. We compute a linear decomposition of the azimuthal modes of the polarization field in radial galactocentric bins. We apply this approach to five low-inclination spiral galaxies with both far-infrared (FIR: 154 μm) dust polarimetric observations taken from the Survey of Extragalactic Magnetism with SOFIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…We will show below that these high-density regions deviating from the local inferred magnetic field often correspond, as expected, to star-forming regions. This association confirms the large angular dispersion of the FIR magnetic fields located in dense regions and the steep depolarization rate with increasing column density measured in nearby spiral galaxies (Lopez-Rodriguez et al 2022;Borlaff et al 2023;Surgent et al 2023).…”
Section: Global Comparison Of Synthetic Fir and Radio Observationssupporting
confidence: 85%
See 2 more Smart Citations
“…We will show below that these high-density regions deviating from the local inferred magnetic field often correspond, as expected, to star-forming regions. This association confirms the large angular dispersion of the FIR magnetic fields located in dense regions and the steep depolarization rate with increasing column density measured in nearby spiral galaxies (Lopez-Rodriguez et al 2022;Borlaff et al 2023;Surgent et al 2023).…”
Section: Global Comparison Of Synthetic Fir and Radio Observationssupporting
confidence: 85%
“…Furthermore, the angular variations of the plane-of-the-sky magnetic field orientations inferred from FIR observations are larger than those measured by the radio magnetic fields (Borlaff et al 2023). Surgent et al (2023) showed that the FIR magnetic field orientations are 7%-25% more disordered than those from the magnetic fields inferred from the radio emission. Note that these variations are at the scales of the angular resolution of the observations, typically 300-500 pc.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation